2018
DOI: 10.1089/ten.teb.2018.0008
|View full text |Cite
|
Sign up to set email alerts
|

Blood Plasma Derivatives for Tissue Engineering and Regenerative Medicine Therapies

Abstract: Platelet-rich plasma (PRP) and its derivatives have been investigated and applied in regenerative medicine. The use of PRP as a supplement of cell culture media has consistently shown to potentiate stem cell proliferation, migration, and differentiation. In addition, the clinical utility of PRP is supported by evidence that PRP contains high concentrations of growth factors (GFs) and proteins which contribute to the regenerative process. PRP based therapies are cost effective and also benefit from the accessib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 90 publications
(95 reference statements)
0
50
0
1
Order By: Relevance
“…In this study, PL-and FB-based scaffold systems were used to provide support for cells, sustain their migratory capabilities, and enhance their pro-regenerative profile. PL and FB scaffolds have been used previously for skeletal muscle regeneration and to develop clinical strategies for bone repair 23,24 but not with WJ-MSCs for neuro-repair studies. Here, we have used such bio-scaffolds to estimate neuroprotective and anti-inflammatory properties of WJ-MSCs and to compare the utility of different scaffolds for possible transplantation to the injured Central Nervous System (CNS).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, PL-and FB-based scaffold systems were used to provide support for cells, sustain their migratory capabilities, and enhance their pro-regenerative profile. PL and FB scaffolds have been used previously for skeletal muscle regeneration and to develop clinical strategies for bone repair 23,24 but not with WJ-MSCs for neuro-repair studies. Here, we have used such bio-scaffolds to estimate neuroprotective and anti-inflammatory properties of WJ-MSCs and to compare the utility of different scaffolds for possible transplantation to the injured Central Nervous System (CNS).…”
Section: Discussionmentioning
confidence: 99%
“…When used with previous platelet activation, it proves to be a cost-effective reservoir of numerous platelet-derived biologically active molecules including growth factors and cytokines, holding a strong potential for improving tissue healing and regeneration [ 1 , 2 , 3 , 4 ]. For this reason, it is widely applied in different areas of medicine such as dermatology and aesthetic medicine [ 5 , 6 , 7 ], plastic surgery [ 8 ], dentistry [ 9 , 10 ], musculoskeletal and sport medicine [ 11 , 12 , 13 , 14 ], ophthalmology [ 15 , 16 ], gynecology [ 17 ], and tissue engineering [ 18 , 19 ]. Its prompt availability from autologous blood, which theoretically disregards concerns of disease transmission or immunogenic reactions, as well as the ease of administration by direct injection in situ not requiring complex equipment or training, represent additional clinical advantages for its use in regenerative medicine protocols [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…PL are rich in several chemokines and GFs such as platelet derived growth factor isoforms (PDGF-AA, -AB and -BB), transforming growth factor-β (TGF-β), insulin-like growth factor-1 (IGF-1), vascular endothelial growth factor (VEGF) and bone morphogenetic protein 2, -4 and -6 (BMP-2, -4, -6). Several works have suggested that PL are a valuable, non-xenogenic alternative to animal derived serum in cell culture(Bieback, 2013) (Turner, Thiele, & Stegemann, 2017) (Burnouf, Strunk, Koh, & Schallmoser, 2016) or combined with biomaterials (Santos, Sigurjonsson, Custodio, & Mano, 2018) (Oliveira, Santo, Gomes, Reis, & Mano, 2015). Physiologically, platelets are known to deliver a broad spectrum of GFs and have a main role in wound healing.…”
Section: Resultsmentioning
confidence: 99%